Eksistensi Manusia dalam Filsafat Pendidikan: Studi Komparatif Filsafat Barat dan Filsafat Islam - Yoyo Hambali; Siti Asiah (Turats, 2011)
The purpose of this paper is intended to explain human existence in the philosophy of education. This paper explores on human existence according to Western philosophy and the Islamic philosophy. This paper uses the method-comparative analysis. This paper shows that problems of human existence (the problem of human being) are an important issue in the philosophy education because education as human needs cannot be separated from the human himself. Humans are “homo educandum”, the creature that can educate and be educated. Education itself is related to the existence of teachers and students as human beings. In this paper, the experts note that western philosophy and Islamic philosophy has a great attention to human existence in which human existence is discussed in the branch of philosophy that both ontology and anthropological philosophy. The thought of Western philosophy is not holistic, very mechanistic, and pragmatic. The thought of Islamic philosophy is eclectic, integral and holistic. In the field of Islamic education which is characterized by an emphasis on the importance of all aspect/dimensions of human being: physical, spiritual, intellect, soul, and mind.